Franchising: Choose wisely - Singapore Management University (Institutional Knowledge at Singapore Management University, 2016)
The Modern Montessori International chain of preschool education centres expanded into 15 countries within 20 years via franchising. Its owner shares the sometimes painful lessons learnt